The decrease in panicle number is the main reason for the yield reduction of japonica rice caused by 1,2,4-trichlorobenzene stress - Yan, Feiyu; Zhang, Guoliang; Liu, Le; Wang, Fang; Zhao, Hongliang; Huang, Zhiwei; Niu, Yuan (Frontiers in Plant Science, 2024)
Persistent organic pollutants seriously affect the growth and development of crops. 1,2,4-Trichlorobenzene (TCB), as one of the most widely used chlorobenzenes, can affect the yield of japonica rice. However, existing research on the effect of TCB on japonica rice yield is not in-depth, the basic understanding of commonality has not yet been formed. In this study, 28 conventional japonica rice varieties were selected to investigate the effects of TCB stress on their yield, yield composition, and TCB accumulation. This study also evaluated the efficiency of conventional tolerance indices in evaluating the TCB stress tolerance of japonica rice. The results showed that TCB caused sustained inhibition of the growth of japonica rice, which was considerably manifested in plant height, root length, SPAD, and dry weight at different growth stages. Under TCB stress, TCB accumulation in various tissues of japonica rice increased sharply. TCB stress reduces the yield of japonica rice by reducing the number of panicles per hill, the number of spikelets per panicle, grain filling percentage, and grain weight. Overall, the results of this study indicate that TCB stress can cause a decrease in yield of japonica rice and the decrease in panicle number is the main reason. The conventional tolerance index can effectively evaluate the tolerance of japonica rice to TCB. The results of this study are substantial for the breeding and cultivation of japonica rice.